Develop a partial discharge data acquisition board in power grid - Liu, Peiran (Nanyang Technological University, 2022)
Partial discharge usually caused the insulation breakdown of the electric equipment. It is necessary to probe it in advance to improve the stability of the power system. When partial discharge occurs, some phenomena come out, such as the electric pulse, ultrasonic waves, electromagnetic radiation, light, chemical reactions, local heating and so on. These phenomena are usually accompanied by some small-amplitude and high-frequency signals. The online test of the partial discharge of the high voltage electric equipment is usually based on these weak phenomena. Since the price of data acquisition boards on the market is very high, a data acquisition board with a simple structure is designed in this paper, which can achieve most functions while achieving a lower price. There are many partial discharge detections now, such as ultrasonic testing, high frequency current method, ultrahigh frequency testing and so on. In this dissertation, the work mainly focuses on developing the data acquisition board. The data acquisition board is composed of the low noise amplifier, a bandpass filter and a variable gain amplifier to drive the ADC. The bandpass filter consists of a Multi-feedback low-pass filter and a Sallen-Key high-pass filter. The dissertation mainly focuses on the parameter of the data acquisition board, such as the gain, the bandwidth, the power dissipation and the noise of the components. And the stability is also important. Then compare the calculation result and simulation result to ensure the final result.